Consistency of side choice in the milking parlour by holstein-friesian cows and its relationship with their reactivity and milk yield - Paranhos da Costa, Mateus J.R [UNESP]; Broom, Donald M. (Elsevier, 2001)
Dairy cows often have to choose which of two sides to enter in the milking parlour. Some cows are very consistent in this choicė, and it is common to assume that when these cows are more disturbed are being milked in their non-preferred side. Such disturbance might involve significantly poor welfare. In order to assess this assumption, we decided to study the behaviour and milk yield of dairy cows and their relationships with side preference in the milking parlour. The study was carried out at Cambridge University Farm, in a two-sided tandem milking parlour. The data collection followed the daily management routine. We recorded the side chosen by each cow (left or right) during 40 milking sessions. Data from 70 cows, which were present in at least 25 milking sessions (mode = 36), were included in the statistical analysis. Cows' reactivity (CR) during premilking udder preparation, time spent fitting the milking cluster (FT), milk yield (MY) and duration of milking (DM) were measured. There was evident individual variation in the consistency of side choice. Individual differences (ANOVA, P < 0.001) were also found in CR, FT, MY and DM; although these variables were not significantly affected by the side or the interaction animal × side (ANOVA, P < 0.05). The comparison between left and right side means (paired t-test) of these variables did not show significant differences (P < 0.05). We concluded that there is no evidence that the cows were discomforted or stressed when milked in the non-preferred side of the milking parlour. © 2001 Elsevier Science B.V.
Keywords: Cattle-milking; Individual differences; Side preference; Temperament; Welfare; Animalia; Bos taurus; Friesia